Age is just a number: Is frailty being ignored in vascular access planning for dialysis?. Issue 2 (March 2022) - Kuningas, Kulli; Inston, Nicholas
Current international guidelines advocate fistula creation as first choice for vascular access in haemodialysis patients, however, there have been suggestions that in certain groups of patients, in particular the elderly, a more tailored approach is needed. The prevalence of more senior individuals receiving renal replacement therapy has increased in recent years and therefore including patient age in decision making regarding choice of vascular access for dialysis has gained more relevance. However, it seems that age is being used as a surrogate for overall clinical condition and it can be proposed that frailty may be a better basis to considering when advising and counselling patients with regard to vascular access for dialysis. Frailty is a clinical condition in which the person is in a vulnerable state with reduced functional capacity and has a higher risk of adverse health outcomes when exposed to stress inducing events. Prevalence of frailty increases with age and has been associated with an increased risk of mortality, hospitalisation, disability and falls. Chronic kidney disease is associated with premature ageing and therefore patients with kidney disease are prone to be frailer irrespective of age and the risk increases further with declining kidney function. Limited data exists on the relationship between frailty and vascular access, but it appears that frailty may have an association with poorer outcomes from vascular access. However, further research is warranted. Due to complexity in decision making in dialysis access, frailty assessment could be a key element in providing patient-centred approach in planning and maintaining vascular access for dialysis.